VD_FINDINFO AP / 2009 / 177 vom 11. März 2009 - VD Tribunal cantonal (2009)
FIXATION DE LA PEINE, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE | 42 al. 4 CP, 43 CP, 47 CP, 71 CP, 411 let. g CPP, 411 let. h CPP, 411 let. i CPP, 415 CPP